DEBRIS FLOW DEPOSITS WITHIN THE PALAEOGENE LAVA FIELDS OF NW SCOTLAND: EVIDENCE FOR MASS WASTING OF THE VOLCANIC LANDSCAPE DURING EMPLACEMENT OF THE ARDNAMURCHAN CENTRAL COMPLEX - Brown D.J.; Bell B.R. (My University, 2007)
Coarse fragmental rocks, previously interpreted as primary pyroclastic accumulations infilling flared vents (Richey JE 1938) “The rhythmic eruptions of Ben Hiant, Ardnamurchan, a tertiary volcano. Bull Volcanol” 2(3):1–21), are re-interpreted as predominantly debris flow deposits, with minor hyperconcentrated and stream-flow deposits, temporally and spatially associated with the Palaeogene Ardnamurchan Central Complex (ACC), NW Scotland. These volcaniclastic rocks are conglomerates and breccias, interbedded with siltstones and sandstones, which formed by surface processes on a dissected landscape, developed in response to shallow emplacement of the ACC. Clast-matrix and photo-statistical analyses allow the palaeo-topography and drainage system to be reconstructed and the development of a palaeo-geographic model for the volcanic landscape. Slabs of basalt, dolerite and sandstone were transported as megablocks during catastrophic, gravity-driven events. Lower energy intervals during volcanic hiatuses are marked by lacustrine-fluvial volcaniclastic siltstones and sandstones preserving palynomorph assemblages. We suggest that shallow intrusion is a plausible initiation mechanism for mass wasting in other large igneous provinces. Historically, deposits of the type described here may have been misidentified as vent facies pyroclastic materials.
Keywords: MASS WASTING; DEBRIS FLOWS; CONGLOMERATES; VOLCANICLASTIC; PALAEOGENE FLOOD BASALTS; ARDNAMURCHAN CENTRAL COMPLEX; PALAEOGEOGRAPHY; Cenozoic::Paleogene; Кайнозой::Палеоген